Sexual harassment among disabilities in Makassar City: An Islamic law perspective - Tulhidayah, Radhiah; Kara, Siti Aisyah; Santalia, Indo; Jafar, Usman; Alwi, Zulfahmi (Universitas Islam Negeri Ar-Raniry, 2024)
The main objective of the research is to find out the risk of sexual harassment of persons with disabilities in Makassar City from the perspective of Islamic Law. This type of research is qualitative research (field research), with the research approach being theological-normative, sociological, and juridical. Primary data sources were eight subjects. The subjects were five women with disabilities, a psychologist, two social workers, and a religious figure. The secondary data is obtained through books, journal articles, government data, laws, fatwas, and research reports by utilizing libraries, online databases, and websites of related institutions. The data collection methods used are observation, interviews, documentation, and reference searches. Data processing and analysis techniques are carried out in three stages: data reduction, presentation/display, and conclusion drawing. The results of this study show, from an Islamic law perspective, that the protection of women with disabilities is supported by principles such as human dignity (al-Karāmah al-Insāniyah), equality (al-Musawah), justice (al-'Adalah), and freedom (al-Hurriyah). Islam underscores the importance of safeguarding and respecting the rights of all individuals, including those with disabilities. Islamic sanctions for sexual harassment can range from ta'zir (discretionary punishments) to had (prescribed punishments), depending on the severity of the offense. These Islamic principles align with human rights standards and provide a foundation for fostering a more equitable and secure environment for women with disabilities. The research implications include the development of an Islamic law-based protection system, raising social awareness, and establishing a support network to create a safe environment for women with disabilities.